Pengembangan pembelajaran dengan model discovery learning menggunakan media pembelajaran lectora inspire di SMA pada pokok bahasan ikatan kimia - Cindy Fitria; Ani Sutiani (ARKA INSTITUTE, 2022)
This study aims to analyze the feasibility of using Lectora inspire learning media based on BSNP criteria; the effect of the discovery learning model on learning outcomes and learning outcomes; and the correlation between motivation and learning outcomes with the discovery learning model using the learning media Lectora inspire. This research is development research using adaptation measures in the ADDIE approach. The research in the implementation phase of using Lectora inspire learning media was carried out with Pre-Experiment Designs in the form of One-Group Pretest-Posttest Designs. The sample selection used a purposive sampling technique. The sample studied was 41 students from SMA Negeri 7 Medan. The instruments used were student learning outcomes tests, modified BSNP questionnaires, and student learning motivation questionnaires. The results of this study indicate that through the development of learning with Lectora inspire learning media using discovery learning models on chemical bonding materials: the average feasibility of using Lectora inspire learning media on all BNSP criteria is a very feasible category (content feasibility = 3.75; language eligibility = 3.79; and presentation feasibility = 3.70); its use has an effect on improving student learning outcomes (with an N-gain score of 0.80); learning achievement obtained with the discovery learning model using the learning media Lectora inspire is higher than the KKM with an average posttest score of 88.21; and students' learning motivation correlated significantly with their learning outcomes.